Association between physical activity and dysmenorrhea intensity among adolescent - Icha Dwi Ipanka; Sholaikhah Sulistyoningtyas (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Dysmenorrhea is one of the most common reproductive health problems among adolescent girls and frequently interferes with daily activities, school attendance, and academic performance. Regular physical activity has been reported to improve blood circulation, reduce prostaglandin production, and stimulate endorphin release, thereby potentially decreasing menstrual pain. However, evidence regarding the association between physical activity and dysmenorrhea among adolescent girls in Sleman remains limited. Purpose: To determine the relationship between physical activity and the intensity of dysmenorrhea among adolescent girls. Method: A quantitative analytical study with a cross-sectional design was conducted among 66 tenth-grade female students selected from a population of 192 students using proportionate stratified random sampling. Physical activity was assessed using the Global Physical Activity Questionnaire (GPAQ), while dysmenorrhea intensity was measured using the Numeric Rating Scale (NRS). Data were analyzed using descriptive statistics and Spearman's rank correlation test with a significance level of p < 0.05. Results: Of the 66 respondents, 57.5% engaged in vigorous physical activity, whereas 45.4% reported no menstrual pain. Spearman's rank correlation analysis demonstrated a statistically significant association between physical activity and dysmenorrhea intensity (Spearman's rho = 0.673; p < 0.001). Higher levels of physical activity were associated with lower menstrual pain intensity among adolescent girls. Conclusion: Physical activity level was significantly associated with dysmenorrhea intensity. However, the direction of the association should be confirmed based on the variable coding and correlation output.